Regional Government Policy in Environmental Management in Autonomy Regional Era to Make Up the National Development - Asri Agustiwi, Hartiwiningsih dan Isharyanto (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Environmental issues in the region have become one of the world's problemsthat surfaced in the last quarter century, including in Indonesia so thatenvironmental issues are very interesting to talk about. The division ofauthority between the central and regional governments which are thendelegated to the regions widely, in relation to the Law on RegionalAutonomy, namely Law No. 23 of 2014 on Regional Government, thisopens the opportunity for the region to determine its policy broadly,especially considering the investment policy in wide open areas in theregion to support the National Development. In this paper the authors usethe type of normative legal research, then the type of data used in thiswriting is the type of secondary data. Secondary data is data obtainedthrough literature study. Secondary data obtained from a number ofinformation or facts obtained indirectly, namely through literature studyconsisting of documents, literature books, and others related to the problemunder study. Techniques used in this writing the author uses the technique ofWriting Libraries is a technique in the form of literature studies of booksand literature and legislation related to the subject matter studied. Theauthority of the relevant area of the Environment shall be contained inArticle 12 of Law Number 23 Year 2014 concerning Regional Government,paragraph (2), letter e. National and Regional Policy in EnvironmentalManagement. In accordance with Law 23 of 2014 on Regional Governmentand Government Regulation no. 25 of 2000 on the Authority of theGovernment and the Authority of Provinces as Autonomous Regions, in thefield of the environment provides political recognition through transfer ofauthority from the central government to the regions. In this case also needto be re-examined various policies that exist in local government so thatthere is no policy in the form of local regulation that harm the environmentand do not pay attention to condition of society which with nationaldevelopment.Keywords : ( Regional Autonomy, Environment and National Development )